Answer :
Answer and Step-by-step explanation:
Given Asin(wt + phi), we know that sin (A + B) = sinAcosB + sinBcosA. This means:
Asin(wt + phi) = Asin(wt)cos(phi) + Asin(phi)cos(wt).
Let Acos(phi) = c2 and Asin(phi) = c1 we have:
Asin(wt + phi) = c2sin(wt) + c1cos(wt)
Answer:
Step-by-step explanation:
In order to prove that Asin(ωt+ϕ) equals c2sin ωt+ c1cos ωt we need use the sin (A+B) sum identity.
The sin sum identity is sin(A+B)= sinA × cosB + cosB × sinA
Now lets plug in our info.
Asin(ωt+ϕ)= (sin wt × cosϕ) + (cos wt × sinϕ)
We know that Asin= c1 and Acos= c2.
Once we input c1 and c2 and solve, our end result becomes c2sin(wt)+c1cos(wt)